Adolescent Pregnancy: Past, Present and Future Trends and Issues - Naomi Farber (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
This collection provides a forum for leading scholars to examine theoretical insights and empirical findings associated with the recent decline in adolescent pregnancy and childbearing internationally, with special attention given to the United States. This recent shift in the incidence of adolescent fertility is notable in its consistency and magnitude; at the same time, however, continuing historic disparities require focused attention on the contemporary meaning of early childbearing in the U.S. as well as across the globe. The widely interdisciplinary contributions focus on demographic trends in adolescent fertility; successful intervention approaches and major "lessons learned" regarding primary pregnancy prevention; identification of key theoretical issues associated with these trends, with particular focus on the existence and meaning of disparities and their implications for youth development and wellbeing.